Frugal innovation: a proposal of an instrument to measurement - Rossetto, Dennys Eduardo (2020)
Submitted by Adriana Alves Rodrigues (aalves@espm.br) on 2020-10-23T12:59:44Z No. of bitstreams: 1 DENNYS EDUARDO ROSSETO ALVES DE ARAUJO.pdf: 3191229 bytes, checksum: b82905bab592ac9f2fc9565d44eaa3c1 (MD5)